2016
DOI: 10.1136/openhrt-2016-000411
|View full text |Cite
|
Sign up to set email alerts
|

Coronary sinus-based percutaneous annuloplasty as treatment for functional mitral regurgitation: the TITAN II trial

Abstract: ObjectiveFunctional (or secondary) mitral regurgitation (FMR) is associated with greater morbidity and worse outcomes in patients with congestive heart failure (CHF) and cardiomyopathy. The Carillon® Mitral Contour System® is a coronary sinus-based percutaneous therapy to reduce FMR. We evaluated the safety and efficacy of a modified version of the Carillon device in the treatment of patients with cardiomyopathy and FMR.Methods36 patients with CHF, depressed left ventricular function (ejection fraction <40%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 22 publications
(18 reference statements)
7
88
0
Order By: Relevance
“…Several studies have shown the safety and efficacy of the device with reduction in mitral regurgitation grade and improvement in exercise capacity, quality of life, [9][10][11] and left ventricular (LV) reverse remodelling. 11,12 The device also reduces MA dilation, but there are no data on the treatment effect on left atrial (LA) enlargement. LA enlargement, however, is associated with a heightened risk of cardiovascular events and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the safety and efficacy of the device with reduction in mitral regurgitation grade and improvement in exercise capacity, quality of life, [9][10][11] and left ventricular (LV) reverse remodelling. 11,12 The device also reduces MA dilation, but there are no data on the treatment effect on left atrial (LA) enlargement. LA enlargement, however, is associated with a heightened risk of cardiovascular events and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…After the deployment of device, manual traction is performed on the delivery system to compress the periannular tissue neighboard of posterior annulus. Several limitations of this device have been reported, including reports of potential nitinol wire fracture with or without clinical events and especially compression of circumflex coronary artery [7]. This technique peri-procedural success is lower than MitraClip according to published studies.…”
Section: Transcatheter Direct or Indirect Mitral Annuloplasty Systemsmentioning
confidence: 93%
“…After 12 months, there was sustained MR reduction and functional capacity. A second‐generation device to avoid previously observed anchor fractures was safe and similarly effective in 36 patients (TITAN II trial) . The effects on clinical outcomes are unknown.…”
Section: Transcatheter Mitral Valve Interventionsmentioning
confidence: 99%